The Influence of Information Quality, System Quality, and E-Service Quality on Repurchase Intention Through Customer Satisfaction Among Online Travel Agency Users - Galih Lintang Ananda Mustika; Euphrasia Susy Suhendra (Indatu Journal of Management and Accounting, 2026)
The purpose of this study is to examine the effects of information quality, system quality, and e-service quality on repurchase intention for airline tickets, with customer satisfaction serving as a mediating variable among Traveloka users. This study employs a quantitative approach using primary data collected through an online questionnaire distributed to 150 respondents who are Traveloka users in Depok City and have purchased airline tickets at least twice. The sampling technique used is non-probability sampling with a purposive sampling method. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that information quality, system quality, and e-service quality have positive and significant direct effects on customer satisfaction. Furthermore, system quality and e-service quality have positive and significant direct effects on repurchase intention. However, information quality does not have a significant direct effect on repurchase intention. The indirect effect analysis reveals that information quality, system quality, and e-service quality positively and significantly influence repurchase intention through customer satisfaction. These findings suggest that online travel agency providers should enhance information quality, system quality, and e-service quality to improve customer satisfaction and increase repurchase intention.